1987
DOI: 10.2134/agronj1987.00021962007900050006x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Nitrogen Utilization Efficiency in Rice Genotypes1

Abstract: Recent research suggests that there is considerable potential for exploiting genotypic differences in N utilization efficiency by crops. Our research attempted to identify traits associated with rice (Oryza sativa L.) genotypes that support maximum grain production with a minimum input of fertilizer. From field experiments on an Andaqueptic Haplaquoll in three consecutive seasons we identified a group of plant parameters associated with efficiency of N utilization to determine if the different genotypes exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 5 publications
1
41
0
Order By: Relevance
“…There is always the risk in overfertilization that it is not a very practical or economical approach to address the problems of mineral nutrition in general. Thus, there is an immediate and pressing need for identifying/developing N-efficient genotypes (Singh et al, 1995, Broadbent et al, 1987. Although not perfect, a genomic approach via genetic selection and plant breeding techniques is helping to develop rice varieties resistant to plant pathogens/pests, and abnormal environmental conditions, including nutrient deficiencies, drought and salinity.…”
Section: Introductionmentioning
confidence: 99%
“…There is always the risk in overfertilization that it is not a very practical or economical approach to address the problems of mineral nutrition in general. Thus, there is an immediate and pressing need for identifying/developing N-efficient genotypes (Singh et al, 1995, Broadbent et al, 1987. Although not perfect, a genomic approach via genetic selection and plant breeding techniques is helping to develop rice varieties resistant to plant pathogens/pests, and abnormal environmental conditions, including nutrient deficiencies, drought and salinity.…”
Section: Introductionmentioning
confidence: 99%
“…Broadbent et al (1987) studied NUE g of 24 genotypes with and without fertilizer-N application. They estimated NUE g using the ratio of panicle weight to total N uptake (WP/TN) and reported that there were significant differences in WP/TN among the genotypes.…”
Section: Genotypic Variation In Nitrogen Use Efficiencymentioning
confidence: 99%
“…Crop growth duration affects NUE g through influencing crop yield and N uptake. Medium-duration genotypes had higher NUE g than short-duration genotypes (Broadbent et al 1987;De Datta and Broadbent 1990). Longer duration could result in a decrease in NUE g (Samonte et al 2006).…”
Section: Plant Traits Related To Nitrogen Use Efficiencymentioning
confidence: 99%
See 2 more Smart Citations